Divergent Cardiac Effects of Angiotensin II and Isoproterenol Following Juvenile Exposure to Doxorubicin - Agostinucci, Kevin; Grant, Marianne K. O.; Seelig, Davis; Yücel, Doğacan; van Berlo, Jop; Bartolomucci, Alessandro; Dyck, Jason R. B.; Zordoky, Beshay N. (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is the most significant risk factor for heart failure in doxorubicin (DOX)-treated childhood cancer survivors. We previously developed a two-hit mouse model of juvenile DOX-induced latent cardiotoxicity that is exacerbated by adult-onset angiotensin II (ANGII)-induced hypertension. It is still not known how juvenile DOX-induced latent cardiotoxicity would predispose the heart to pathologic stimuli that do not cause hypertension. Our main objective is to determine the cardiac effects of ANGII (a hypertensive pathologic stimulus) and isoproterenol (ISO, a non-hypertensive pathologic stimulus) in adult mice pre-exposed to DOX as juveniles. Five-week-old male C57BL/6N mice were administered DOX (4 mg/kg/week) or saline for 3 weeks and then allowed to recover for 5 weeks. Thereafter, mice were administered either ANGII (1.4 mg/kg/day) or ISO (10 mg/kg/day) for 14 days. Juvenile exposure to DOX abrogated the hypertrophic response to both ANGII and ISO, while it failed to correct ANGII- and ISO-induced upregulation in the hypertrophic markers, ANP and BNP. ANGII, but not ISO, worsened cardiac function and exacerbated cardiac fibrosis in DOX-exposed mice as measured by echocardiography and histopathology, respectively. The adverse cardiac remodeling in the DOX/ANGII group was associated with a marked upregulation in several inflammatory and fibrotic markers and altered expression of Ace, a critical enzyme in the RAAS. In conclusion, juvenile exposure to DOX causes latent cardiotoxicity that predisposes the heart to a hypertensive pathologic stimulus (ANGII) more than a non-hypertensive stimulus (ISO), mirroring the clinical scenario of worse cardiovascular outcome in hypertensive childhood cancer survivors.